Determinants and survival benefits of achieving textbook outcome for intrahepatic cholangiocarcinoma in the era of neoadjuvant therapy - Hu, Jiawei; Wang, Yihang; Diao, Haoran; Miao, Shuangda; Zhang, Xiaoxiao; Li, Qi; Pan, Yanzhi; Jin, Yun; Yu, Yuanquan; Li, Jiangtao (Frontiers in Oncology, 2026)
BackgroundIntrahepatic cholangiocarcinoma (ICC) is a highly aggressive malignancy with a poor prognosis. Radical resection is the modality to cure patients with ICC. Thus, surgical quality is the key prognostic factor for survival. Textbook outcome (TO) is a multidimensional composite indicator reflecting surgical care quality. However, the association between neoadjuvant therapies—particularly those incorporating targeted and/or immunotherapeutic agents into chemotherapy regimens—and the attainment of TO in ICC remains unclear and warrants further investigation.Materials and methodsThis retrospective study analyzed 187 patients with ICC who underwent curative resection. TO was defined as the simultaneous achievement of R0 resection, with no perioperative blood transfusion, no postoperative complications, no mortality within 30 days, no unplanned readmission within 30 days, and a postoperative length of stay not exceeding the 75th percentile. Logistic regression was used to identify factors associated with TO, with further analysis focused on the role of neoadjuvant therapy. Cox regression was used to evaluate prognostic factors for overall survival (OS), and a prognostic nomogram incorporating TO was developed and validated.ResultsTO was achieved in 53 patients (28.3%), which was significantly associated with improved OS (p = 0.003) and recurrence-free survival (p < 0.001). Multivariable analysis identified neoadjuvant therapy [odds ratio (OR) = 2.687, p = 0.014], higher body mass index, higher albumin levels, lower carcinoembryonic antigen levels, and reduced blood loss as independent predictors of TO. Combination neoadjuvant regimens (chemotherapy plus targeted/immunotherapy; OR = 2.647, p = 0.009) were the primary contributors to this positive association. A nomogram integrating TO, lymph node metastasis, prothrombin time, and adjuvant therapy demonstrated excellent predictive accuracy for survival (1-year area under the curve = 0.891).ConclusionAchieving TO is associated with significantly improved survival in patients with ICC. Combined neoadjuvant therapy, including targeted or immunotherapy, is an independent positive predictor of TO, which challenges conventional perspectives. The proposed TO-integrated nomogram is a practical tool for prognostic prediction and surgical quality assessment.